Journey through mathematics creative episodes in its history - González-Velasco, Enrique A.; SpringerLink (Online service). (New York, New York Springer New York, 2011)
This book offers an accessible and in-depth look at some of the most important episodes of two thousand years of mathematical history. Beginning with trigonometry and moving on through logarithms, complex numbers, infinite series, and calculus, this book profiles some of the lesser known but crucial contributors to modern day mathematics. It is unique in its use of primary sources as well as its accessibility; a knowledge of first-year calculus is the only prerequisite. But undergraduate and graduate students alike will appreciate this glimpse into the fascinating process of mathematical creation. The history of math is an intercontinental journey, and this book showcases brilliant mathematicians from Greece, Egypt, and India, as well as Europe and the Islamic world. Several of the primary sources have never before been translated into English. Their interpretation is thorough and readable, and offers an excellent background for teachers of high school mathematics as well as anyone interested in the history of math
Preface -- 1 Trigonometry -- 2 Logarithms -- 3 Complex Numbers -- 4 Infinite Series -- 5 The Calculus -- 6 Convergence -- Bibliography -- Index
Electronic reproduction.
Keywords: Mathematics -- History; Mathematics